Effect of Stator Vane on the Performance of the Savonius Wind Turbine - Yoga Arob Wicaksono (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2019)
The turbulent air flow conditions in the urban area have a large effect on the performance of Savonius rotor wind turbines. To overcome this problem, a new design of the stator vane needs to be made. the stator vane has the ability to direct wind to the turbine rotor and increase air speed by utilizing throttling effects. Thus, the performance of the Savonius wind turbine can increase. In this study, the Savonius type vertical wind turbine is configured with three stator vane designs that have slope angles: 60o, and 70o. Performance testing is carried out at angles: 0o, 30o, and 60o towards the midpoint of the stator vane to find the direction of direction coming from the best wind on each stator vane design. All configurations are analyzed using an experimental wind tunnel open testing scheme with a wind speed range of 3-5 m/s. The parameters produced from the experiment include: power coefficient (Cp), torque coefficient (Ct) and Tip Speed ​​Ratio (TSR). The results showed that the stator vane with 60o inclination angle was able to increase Cp 35.66% in the 60o incoming wind direction.